Overview of mom's confidence when planning to return low birth weight baby from the hospital - Ari Setyawati; Lumastari Ajeng Wijayanti; Fithri Ratnasari; Hesti Wahyuni; Indrawati Aris Tyarini (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Babies with low birth weight are one of the health problems often faced by mothers and families in various countries, including Indonesia. The return of babies with low birth weights from the hospital became a critical stage in their care after a period of intensive hospitalization. Objective: Describe the mother's confidence level when planning to return a baby with a low birth weight to the hospital. Method: quantitative research with a descriptive design involving 29 respondents. This study used non-probability and consecutive sampling techniques to determine subjects who met the inclusion criteria. The measuring instrument uses the Maternal Confidence Questionnaire Instrument, and the analysis results are descriptive data equipped with tables. Results: Most of the self-confidence of mothers planning to return home with high-birth-weight babies from the hospital was high among 16 respondents (55.2%). Factors that influence a mother's confidence include previous experience caring for a child, social support from family and friends, information and education provided by medical personnel, and an adequate financial condition and environment for the care of the baby. Conclusion: The mother's self-confidence plays a crucial role in planning the return of a low-birthweight baby from the hospital. Social support, knowledge of baby care, interaction with health workers, and understanding of the baby's health condition contribute to the mother's confidence. A holistic approach involving adequate social support, information and education, and financial and environmental readiness to increase maternal confidence in caring for a low-birth-weight baby after discharge from the hospital